The Wild Rice Locus CTS-12 Mediates ABA-Dependent Stomatal Opening Modulation to Limit Water Loss Under Severe Chilling Stress - Cen, Weijian; Zhao, Wenlong; Ma, Mingqing; Lu, Siyuan; Liu, Jianbin; Cao, Yaqi; Zeng, Zhenhua; Wei, Hanxing; Wang, Shaokui; Li, Rongbai; Luo, Jijing (Frontiers in Plant Science, 2020)
An isogenic line (NIL) DC90 which was generated by introgressing a wild rice locus CTS-12 into the 9311 background confers the chilling tolerance phenotype. Here, our pilot trials showed that chilling tolerance was positively correlated with ABA biosynthesis. To understand how CTS-12 mediated the ABA-dependent multi-levels of regulation, the integration of transcriptomic and metabolomic profiling using the two-way orthogonal projections to latent structures (O2PLS) and discriminant analysis (OPLS-DA) modeling was performed to investigate the mechanisms underlying chilling tolerance. Our results revealed that metabolic shifts, including the activation of stachyose biosynthesis, amino acid metabolism pathways, phenylpropanoid/flavonoid biosynthesis, and ABA biosynthesis, and perturbation of glycolysis, occurred under chilling treatment; in the recovery period, glutamate-related pathways, β-alanine biosynthesis and degradation, and serotonin biosynthesis pathways were differentiated between 9311 and DC90. Particularly, the differentially accumulated metabolites (DAMs) and differentially expressed genes (DEGs), including galactinol, β-alanine, glutamate, naringenin, serotonin, abscisic acid (ABA), and LOC_Os03g44380 (OsNCED3), might be involved in the chilling tolerance variation of 9311 and DC90. CRISPR/Cas9-edited OsNCED3 resulted in chilling sensitive of japonica rice ZH11, demonstrating the involvement of ABA pathway in chilling stress response. In addition, chilling tolerance of rice was associated with the balance of water uptake and loss that was modulated by stomatal movement under chilling stress. Therefore, we speculated that the CTS-12-mediated ABA signaling pathway leads to transcriptional regulation of chilling-responsive genes and, in turn, triggers metabolic shifts to coordinately regulate the stomatal movement of guard cells. The results of this study improve our understanding of the multilevel regulation of wild rice in response to chilling stress.